2016
DOI: 10.3791/53266
|View full text |Cite
|
Sign up to set email alerts
|

A General Method for Evaluating Deep Brain Stimulation Effects on Intravenous Methamphetamine Self-Administration

Abstract: Substance use disorders, particularly to methamphetamine, are devastating, relapsing diseases that disproportionally affect young people. There is a need for novel, effective and practical treatment strategies that are validated in animal models. Neuromodulation, including deep brain stimulation (DBS) therapy, refers to the use of electricity to influence pathological neuronal activity and has shown promise for psychiatric disorders, including drug dependence. DBS in clinical practice involves the continuous d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…General limitations of HF-DBS have been extensively reviewed elsewhere 24,25 . One of the challenges for the experiment here is also the need for an excellent surgical technique and for the ongoing care of surgical anatomical locus.…”
Section: Discussionmentioning
confidence: 99%
“…General limitations of HF-DBS have been extensively reviewed elsewhere 24,25 . One of the challenges for the experiment here is also the need for an excellent surgical technique and for the ongoing care of surgical anatomical locus.…”
Section: Discussionmentioning
confidence: 99%
“…As a typical neurosurgical procedure, DBS has been used to cure abnormal neuronal firing patterns that result from certain diseases, such as Parkinson's disease, essential tremors, and dystonia (Flora et al, 2010 ; Miocinovic et al, 2013 ). However, careful wound care and personal hygiene are needed to protect DBS hardware and to avoid additional negative impacts after the surgery (Umemura et al, 2003 ; Blomstedt and Hariz, 2006 ; Batra et al, 2016 ). Studies on non-invasive brain stimulation that does not require built-in hardware are accumulating rapidly.…”
Section: Introductionmentioning
confidence: 99%
“…Previous experiments indicated that this initial prolonged and "easy" access results in the majority of rodents acquiring significant drug-taking behavior in less than 1 week. 3 During the 2nd and 3rd weeks of training, rats underwent 2-hour daily sessions at approximately the same time Monday through Friday, again on an FR1 schedule of reinforcement culminating in the rats developing a baseline intake termed "maintenance." Maintenance was operationally defined as stable, intense responding for which the total number of methamphetamine infusions across each session varied less than approximately 10% for 3 consecutive sessions and the cumulative number of infusions across the 1st 30 minutes was greater than, or equal to, the cumulative number of infusions during the 2nd 30 minutes.…”
Section: Operant IV Methamphetamine Self-administrationmentioning
confidence: 99%
“…This criterion ensured that the rats developed a drug-loading pattern that indicated addictive behavior 1 and not simply casual use by the time treatment was initiated. 3 Once maintenance had been established, rats were counterbalanced based on total baseline 2-hour IV methamphetamine infusions and divided in 2 groups, active stimulation (DBS) and sham stimulation (sham).…”
Section: Operant IV Methamphetamine Self-administrationmentioning
confidence: 99%